Relationship Corruption and Economic Growth ASEAN Countries - LESTARI, WINDA RIKA; ., SUNARMI; WAHYUDI, HERU (Journal of Ecohumanism, 2024)
Corruption is a detrimental act for many people, especially related to the economy. Various groups widely discuss corruption and economic growth from academia, government, and the private sector. This is even more complex when coupled with competitiveness between countries and democratic systems. So this study aims to analyze the influence of global competitiveness, corruption and democracy on economic growth in ASEAN countries. This study used panel data analysis methods in 7 ASEAN countries from 2014-2019. The seven countries are Indonesia, Malaysia, Thailand, the Philippines, Vietnam, Laos, and Cambodia. It is related to economic growth, corruption, and competitiveness in ASEAN countries. The results of this study show that corruption brings mudhorot but has yet to be significant to economic growth. Another interesting finding is that democracy negatively affects global competitiveness and increases economic growth. This research can be one of the government’s policy recommendations by increasing economic growth through strict enforcement against corruption and increasing global competitiveness. To realize economic growth that prospers society requires the role of the government through increasing human and institutional resources to support other competitiveness factors that focus on technological, environmental, and innovation aspects